2023
DOI: 10.1590/1980-549720230009.supl.1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of morbidities, and risk and protective factors for noncommunicable diseases in elderly residents in Brazilian capitals

Abstract: Objective: To analyze the temporal trends of prevalence of morbidities, risk and protection factors for noncommunicable diseases in elderly residents in Brazilian capitals between 2006 and 2021. Methods: A time series study with data from the Surveillance System of Risk and Protective Factors for Chronic Diseases by Telephone Inquiry. The variables analyzed were: high blood pressure, diabetes, smoking, overweight, obesity, consumption of alcoholic beverages, soft drinks, fruits and vegetables, and the practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
2
0
3
Order By: Relevance
“…Food markers signal the healthiness of a population's food consumption, contributing to food and nutritional surveillance 10,21,22 and the formulation and implementation of public policies 10,22 . It is observed that population surveys have included their evaluation in their protocols, even enabling the understanding of the temporal evolution of food consumption 10,23,24,25 and different cuts in the analysis 26 . In times of health emergency, Steele and collaborators 27 analyzed changes in markers of healthy and unhealthy eating when evaluated before and during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Food markers signal the healthiness of a population's food consumption, contributing to food and nutritional surveillance 10,21,22 and the formulation and implementation of public policies 10,22 . It is observed that population surveys have included their evaluation in their protocols, even enabling the understanding of the temporal evolution of food consumption 10,23,24,25 and different cuts in the analysis 26 . In times of health emergency, Steele and collaborators 27 analyzed changes in markers of healthy and unhealthy eating when evaluated before and during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Soma-se, ainda, a ausência de políticas regulatórias nos últimos anos, por exemplo no controle dos alimentos ultraprocessados, e o baixo incentivo à produção e ao acesso à alimentação de qualidade, como frutas e hortaliças, pelo elevado custo, reduzindo seu consumo, em especial junto à população de baixa renda 26,36,37 . Além disso, as graves crises sanitária, social e política no Brasil se refletiram na piora dos indicadores socioeconômicos no Brasil, acentuando as desigualdades já maximizadas pelas medidas de austeridade e a redução de políticas de proteção social adotadas previamente no país [38][39][40] .…”
Section: Discussionunclassified
“…O modelo teórico do estudo foi desenvolvido levando em consideração as relações previamente identificadas na literatura, as quais são variáveis relevantes para o tema central da pesquisa, que é a gestão da medicação de uso contínuo pela pessoa idosa. Em estudos sobre pessoas idosas e suas medicações, têm-se destacado a consideração dos aspectos demográficos, socioeconômicos e de saúde, uma vez que são elementos cruciais para compreender diversas associações relacionadas aos desfechos de saúde desta população (De Faria Pizzatti et al, 2022;Silva et al, 2023). Nesta pesquisa, estimulam os autores na busca de diferentes histórias, experiências, opiniões e conhecimentos, uma gama ampla de informações e insights valiosos para o entendimento do tema proposto.…”
Section: Fonte: Autoresunclassified
“…A diabete faz uns três eu acho(...)" Mulher, 73 anos "(...)Eu tenho problema de é(...) [pensativo] vamos dizer assim, de pressão, é colesterol, diabete e o que mais que eu vou dizer pra ti(...)labirintite. Faz mais ou menos uns dez anos(...)" Homem, 80 anos "(...)No caso eu tenho problema de coração, pressão(...)É gordura, assim(...)Eu tomava para o coração desde que eu me consultei, tem de dois para três anos e daí esse remédio para pressão, acho que vai fazer uns seis meses(...)" Homem, 71 anos De acordo com Silva et al (2023), as doenças crônicas não transmissíveis são frequentes na população idosa e podem ser compreendidas em quatro grupos principais: cardiovasculares, câncer, doenças respiratórias crônicas e diabetes. Destacamse, entre essas, as doenças cardiovasculares e o diabetes mellitus, mencionados em quase todas as falas.…”
Section: Compreensão Da Condição De Saúdeunclassified